Oceans 2010 MTS/Ieee Seattle 2010
DOI: 10.1109/oceans.2010.5664518
|View full text |Cite
|
Sign up to set email alerts
|

Single beacon navigation: Localization and control of the MARES AUV

Abstract: This paper addresses the simultaneous localization and control of an AUV using a single acoustic beacon. To determine its horizontal position, the AUV fuses distances to the single beacon with dead reckoning data, heading and longitudinal velocity. A particle filter and an extended Kalman filter are implemented and compared in terms of performances. As this is an ill-posed problem, special guidance laws are derived so that the overall horizontal positioning error remains bounded. Besides presenting the derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…The main shortcoming of this approach is that its performance depends on the vehicle's trajectory [2], since long paths away from or towards the beacon result in unbounded position error growth. However, certain studies relating the trajectory of the vehicle to the observability of the system [4] and derive conditions of observability for the system in single range navigation [5]. One way to overcome this problem is having a transponder attached to a vehicle with the ability of determining its position with minimal uncertainty so that other vehicles can use it as a beacon for localization purposes.…”
Section: Acoustic Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The main shortcoming of this approach is that its performance depends on the vehicle's trajectory [2], since long paths away from or towards the beacon result in unbounded position error growth. However, certain studies relating the trajectory of the vehicle to the observability of the system [4] and derive conditions of observability for the system in single range navigation [5]. One way to overcome this problem is having a transponder attached to a vehicle with the ability of determining its position with minimal uncertainty so that other vehicles can use it as a beacon for localization purposes.…”
Section: Acoustic Localizationmentioning
confidence: 99%
“…Since the EKF is computationally efficient [13], it is commonly used for state estimation in robotics, and UUV localization is no exception. The EKF is widely used with many localization techniques [2], as well as in many single beacon localization implementations [14], [4] and in CN [10].…”
Section: Filtersmentioning
confidence: 99%
“…Such system is complex and the task of deriving control laws that ensure stability is not trivial, having led to order reduction in several works (see Ferreira, Matos, Cruz & IEEE (2010);Fossen (1994); Teixeira et al (2010), for example). By taking advantage of the body shape symmetries and of the configuration of the actuators on the body, it is usual to decouple the complex motion in more elementary ones.…”
Section: Fig 2 Body Frame and Inertial Frame Referentialsmentioning
confidence: 99%
“…That approach is common in literature concerning marine applications, e.g. Ferreira et al (2010). In MorenoSalinas et al (2013) optimal trajectory to unknown underwater target is found by maximizing Fisher Information Matrix determinant.…”
Section: Introductionmentioning
confidence: 99%